1998
DOI: 10.1016/s0031-9201(98)00101-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling planetary dynamics by using the temperature at the core–mantle boundary as a control variable: effects of rheological layering on mantle heat transport

Abstract: In planetary convection, there has been a great emphasis laid on the usage of the Rayleigh number as a control parameter for describing the vigor of convection. However, realistic mantle rheology not only depends on temperature, pressure, strain-rate and composition, but also on the nature of the dominant creep mechanism, which varies with pressure and also with temperature. It is difficult to study the effects of varying influences from the convective strength without also changing the mantle flow law in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Whereas the average viscosity of deeper mantle under present‐day conditions can be inferred from geophysical observations such as the geoid and postglacial rebound [e.g., Hager et al , 1985; Mitrovica and Forte , 1997], its temperature dependency must be estimated through experimental studies, which are still difficult to conduct at lower mantle conditions [e.g., Karato et al , 1995]. Also, we can only speculate at this point how different deformation mechanisms, such as diffusion and dislocation creep, might compete in the lower mantle [ Karato , 1998], and van den Berg and Yuen [1998] suggested that, under certain conditions, heat flow scaling for the lower mantle may resemble that of Christensen [1985a]. Alternatively, Solomatov [1996] suggested that if the lower mantle is mainly deformed by diffusion creep, which is known to be very sensitive to grain size, the kinetics of grain growth may reverse the temperature dependency of lower mantle viscosity; that is, hotter mantle may become stiffer because grains would grow faster at higher temperatures.…”
Section: Geophysical Perspectives: Thermal Evolution Of Earthmentioning
confidence: 99%
“…Whereas the average viscosity of deeper mantle under present‐day conditions can be inferred from geophysical observations such as the geoid and postglacial rebound [e.g., Hager et al , 1985; Mitrovica and Forte , 1997], its temperature dependency must be estimated through experimental studies, which are still difficult to conduct at lower mantle conditions [e.g., Karato et al , 1995]. Also, we can only speculate at this point how different deformation mechanisms, such as diffusion and dislocation creep, might compete in the lower mantle [ Karato , 1998], and van den Berg and Yuen [1998] suggested that, under certain conditions, heat flow scaling for the lower mantle may resemble that of Christensen [1985a]. Alternatively, Solomatov [1996] suggested that if the lower mantle is mainly deformed by diffusion creep, which is known to be very sensitive to grain size, the kinetics of grain growth may reverse the temperature dependency of lower mantle viscosity; that is, hotter mantle may become stiffer because grains would grow faster at higher temperatures.…”
Section: Geophysical Perspectives: Thermal Evolution Of Earthmentioning
confidence: 99%
“…The applied mantle rheology is based on a composite rheological model combining both Newtonian and non-Newtonian £ow, corresponding to di¡usion and dislocation creep respectively [14,27,29,30]. We use an Arrhenius relation for each of the £ow components for both mantle and crustal materials :…”
Section: Rheological Modelmentioning
confidence: 99%
“…can be transformed into a viscosity expression [see van den Berg and Yuen , 1998]: For values of n unequal to unity, η k introduces a nonlinearity through in the momentum [ van den Berg et al , 1993].…”
Section: Numerical Model Setupmentioning
confidence: 99%